I. Tasheva. Medical humanities. Themes, terms, translation (Contrastive Linguistics, 2024)
Ивета Ташева. Медицинска хуманитаристика. Теми, термини, превод. София: Сиела, 2022. 164 с.The text presents the first work by a Bulgarian author dedicated to the under-studied area of medical humanities in our country. An overview of the thematic content of the book, as well as its structure, is offered. The strengths of the book are highlighted and the readership for which it will bring the most substantial benefit is identified. Argumentation is provided for recognizing the monograph as a pioneering work in the chosen scientific field.